2018
DOI: 10.2147/ndt.s185295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Xiaoyaosan on depressive-like behaviors in chronic stress-depressed rats through regulating tryptophan metabolism in hippocampus

Abstract: BackgroundTryptophan metabolism has always been considered to play a vital role in mental disorder diseases, and how traditional Chinese formula Xiaoyaosan regulates the tryptophan metabolism is a complement to the pathogenesis of depression. This study established a depression rat model by the chronic immobilization stress (CIS) method and observed the change in tryptophan metabolism in hippocampus and the effects of Xiaoyaosan.MethodsForty-eight male Sprague Dawley (SD) rats were randomly divided into the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 55 publications
2
22
0
2
Order By: Relevance
“…In the CUMS induction procedure, rats were successively exposed to a variety of mild stressors, mimicking the effect of chronic stress on promoting depression and inducing a number of long-term physical, behavioral, neurochemical, and neuroendocrine alterations similar to those observed in depressed patients (Liu et al, 2012). Our previous studies have confirmed that the dose of Xiaoyaosan based on dose conversion of an average adult body weight of 60 kg/d has an antidepressant effect on chronically stressed rats (Jiao et al, 2019). Therefore, according to the daily dosage for adults in clinical practice, the rats in the Xiaoyaosan group were treated with Xiaoyaosan at 2.224 g/kg/d for the intervention in this study.…”
Section: Discussionmentioning
confidence: 72%
“…In the CUMS induction procedure, rats were successively exposed to a variety of mild stressors, mimicking the effect of chronic stress on promoting depression and inducing a number of long-term physical, behavioral, neurochemical, and neuroendocrine alterations similar to those observed in depressed patients (Liu et al, 2012). Our previous studies have confirmed that the dose of Xiaoyaosan based on dose conversion of an average adult body weight of 60 kg/d has an antidepressant effect on chronically stressed rats (Jiao et al, 2019). Therefore, according to the daily dosage for adults in clinical practice, the rats in the Xiaoyaosan group were treated with Xiaoyaosan at 2.224 g/kg/d for the intervention in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Thus, our results showed that antidepressant treatment in stressed rats, compared with placebo, caused an increase in the mRNA expression of Tph2 in the cerebral cortex. Similarly, Jiao et al (2019) showed that chronic immobilization stress (CIS) decreased the mRNA and protein expression of Tph2 in the hippocampus, whereas fluoxetine normalized these effects.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, high protein expression of Ido1 may contribute to the inhibition of serotonin production (Myint et al 2007;Wichers et al 2005). Jiao et al (2019) found that CIS increases the level of mRNA and protein expression in the hippocampus and that these effects are normalized by fluoxetine. In turn, our results showed that venlafaxine treatment in stressed rats caused a reduction in Ido1 protein expression in the basal ganglia.…”
Section: Discussionmentioning
confidence: 98%
“…Inflammatory cytokines may act as modulators of 5-HT (serotonin) receptors, and upregulate indoleamine 2,3dioxygenase (IDO), resulting in anxiety-like disorders (Myint and Kim, 2003). The antidepressant-like effects of XYS were associated with downregulation of peripheral IL-1β, IFNγ, TNF-α, and IL-6, and increased synthesis of tryptophan hydroxylase (TPH) and IDO, which play a role in promoting 5-HT synthesis (Jiao et al, 2019). XYS significantly inhibited TNF-α release in serum and the hippocampus through activation of the TNF-α/JAK2-STAT3 pathway, as shown in our preliminary study (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%